Analisis Pengaruh Marketing Mix Syariah Terhadap Kepuasan Konsumen (Studi Kasus : ETED Coffe Jambi ) - Muhammad Imam Ghazali; Lucky Enggrani Fitri; Muhammad Roihan (JOURNAL OF SHARIA ECONOMICS, 2024)
In the current era, the food and beverage industry is growing rapidly and is booming in Indonesia. One of the most popular types of food and beverage industry is restaurants. Many restaurants can be found in the city center and corners of the city, ranging from large to small restaurants. The purpose of this research is to determine the effect of the Sharia 4p marketing mix (product, price, Place and promotion) on consumer satisfaction. This research uses a quantitative method with a population of all ETED Coffee Jambi consumers. The sampling method uses purposive sampling, determining the number of samples using the Cochran formula with a result of 100 respondents. Data collection uses a questionnaire. Questionnaire data were processed using SPSS. The research results show that product and place influence consumer satisfaction at ETED Coffe Jambi, while price and promotion do not influence consumer satisfaction at ETED Coffe Jambi. Place is the most dominant variable influencing consumer satisfaction at ETED Coffee Jambi.